ASSESSING IRON DEFICIENCY AS RISK FACTOR FOR FEBRILE SEIZURES IN CHILDREN BETWEEN SIX MONTHS AND FIVE YEARS OF AGE - SYED , U; IKRAM , F; NAWAZ , R; NAWAZ , S; TABUSSAM , S; ZAMIR , S (Biological and Clinical Sciences Research Journal, 2024)
This case-control study was conducted from September 2023 to December 2023 at the Department of Pediatrics in Pak Emirates Military Hospital, Rawalpindi. The study aimed to determine the relationship between iron deficiency and the development of febrile seizures in children. A total of 150 patients aged between 1 and 6 years, with a history of febrile seizures and currently suffering from pyrexia, were included in the study. Children with a history of recent febrile seizures, structural/organic brain lesions, congenital metabolic/chromosomal anomalies, non-febrile seizures, delayed milestones, or those who were on medications that altered serum iron levels within the past six months were excluded. All participants were assessed for serum iron, ferritin, total iron binding capacity, magnesium, zinc, and calcium at enrollment. Patients were observed for the development of febrile seizures until they were afebrile for twenty-four continuous hours. Of the total sample, the mean age was 3.41 ± 1.51 years, and 83 (55.3%) were male. Patients with a transferrin saturation below 6.5% had a higher adjusted odds ratio (aOR) of 3.96 (CI 95% 1.29 – 12.18, p=0.016) for developing febrile seizures during a pyrexial illness. Similarly, patients with hypozincaemia, defined as a serum zinc level <65 μg/dL, had an aOR of 2.54 (CI 95% 1.13 – 5.67, p=0.023). The study concluded that low serum levels of iron were associated with a higher risk of developing febrile seizures in pyrexial children with a history of the disorder.